Metamorfoza Kultury i sektora kreatywnego w gospodarce ze szczególnym uwzględnieniem propozycji i środków UE - Dziurdzia, Konrad (Gospodarka w Praktyce i Teorii, 2011)
This article outlines the changing role of culture in modern economy. According to European examinations and researches (including the European Commission), culture is one of the biggest and most dynamically developing employers of Europe, supporting increasingly domestic economies, particularly at the regional level. According to many economists, for instance David Throsby (Professor of Economics at Macquarie University in Sydney ), countries, which are not investing in culture at the age of innovative economies cannot function properly. Culture is no longer perceived only in terms of some aesthetic values but is more often regarded as an economical motor. Moreover, the definition of culture applies now to a very broad range of activities, including creative sectors, which are using cultural resources. Culture becomes a web of different sectors. Culture has a direct and indirect impact on economy, especially in the social sphere, it may also strongly affect economic transformations of areas, characterized by low level of general investments. Furthermore, it becomes an object of scientific and economical analyses. Many European countries are demonstrating an interest in the economics and culture, Great Britain or Germany for example – adapting widely culture for economic and social purposes. However this process needs a great deal of support, it is not possible without coherent promotional and educational system, deeply hierarchical model, active participation of non-government organizations, a huge amount of plans and assistance programs dedicated to culture at the local, regional and domestic level, as well as wide non-profit social contribution into the bloom of this increasingly important branch. The idea of profitable culture should be attached to national development strategies. We should create appropriate mechanisms, changing the social attitude towards culture, harnessing informative and educational campaigns raising public awareness of the notion of National Heritage (already at the level of basic education). Long-term programs aiming cultural education are compulsory, within different aspects of its activity. Culture fulfills multiple purposes important for the economy, it stimulates : the labour market, the entrepreneurship of private, public institutions and the society, development of new technologies, tourism, development of professional qualifications (in particular shaping the idea of lifelong learning), other industries. The proportion of well-educated employees in the cultural & creative sector is significant, what was proven in British examinations. Finally, culture allows Poland to apply for a huge financial aid from the EU funds: Culture Programme, European Capital of Culture, Media 2007 Programme, Digital Libraries initiatives, Lifelong Learning Programme or Europe for Citizens project. The role of culture shouldn’t be underestimated at the time of economic chaos in Europe, when governments are deciding on budget cuts. To some extent the article is answering a question, whether the culture should undergo additional funding now, so when the national debts are growing, or it would be illogical.